Multi-response Characteristics Optimization of a Paper-based Composite using Taguchi Method and Particle Swarm Optimization - Pangestu, Phengky; Qurrota Ayun, Azizah Hadny; Wulandari, Rizca Tri; Nabilah, Ekty; Pujiyanto, Eko (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2020)
Our dependency towards wood has reduced the number of forests especially in Indonesia. Hence, many people tried to use another material as a replacement of wood. One of them is composite. Department of Industrial Engineering Universitas Sebelas Maret has developed paper-based composite using newspaper waste in Praktikum Perancangan Teknik Industri (PPTI) II. Unfortunately, the quality of composite is not so good. This paper tried to understand the effect of factors to responses and discover the best combination of factors to obtain the best responses. The responses of this experiment are tensile strength, bending strength and impact value. The factors of this experiment are paper pulp, PVAc glue and water. Taguchi method is used to find the appropriate orthogonal array and Particle Swarm Optimization method to find the optimum combination of the factors. Orthogonal array used in this experiment is L9 (34).  Through analysis, all of the factors are significant to tensile and bending strength, but they are not significant to impact value. The best combination of factors is 175 grams paper pulp, 130 grams PVAc glue and 175 ml water. Optimum results obtained for tensile strength is 0.7595 N/mm2, bending strength is 4.873 N/mm2 and impact value is 0.0138 J/mm2.